P2KP Sebagai Sarana Pemberdayaan untuk Pengentasan Kemiskinan - - Sukidjo (Universitas Negeri Yogyakarta, 2005)
Poverty is a major problem of economic development, because of that the economic development is directed to reduce the poverty. Since poverty is a complex and multidimensional problem including economic, culture and structural, therefore it is reasonable if the program to overcome that problem apply a comprehensive approach instead of merely of economic aspect. Many safety net program have been implemented to eradicate poverty, such as: food aids program, IDT, PDM-DKE, and P2KP. Among those programs, P2KP is thought as a suitable program to society in eradicating poverty since P2KP involves principles of democracy, participation, transparency and decentralization.